The impact of social deprivation on the response to a randomised controlled trial of a weight management intervention (BeWEL) for people at increased risk of colorectal cancer - Fisher, A.; Craigie, A. M.; Macleod, M.; Steele, R. J. C.; Anderson, A. S. (Journal of human nutrition and dietetics, 2018)
Background Although 45% of colorectal cancer (CRC) cases may be avoidable through appropriate lifestyle and weight management, health promotion interventions run the risk of widening health inequalities. The BeWEL randomised controlled trial assessed the impact of a diet and activity programme in overweight adults who were diagnosed with a colorectal adenoma, demonstrating a significantly greater weight loss at 12 months in intervention participants than in controls. The present study aimed to compare BeWEL intervention outcomes by participant deprivation status. Methods The intervention group of the BeWEL trial (n = 163) was classified by the Scottish Index of Multiple Deprivation (SIMD) quintiles into ‘more deprived’ (SIMD 1–2, n = 58) and ‘less deprived’ (SIMD 3–5, n = 105). Socio‐economic and lifestyle variables were compared at baseline to identify potential challenges to intervention adherence in the more deprived. Between group differences at 12 months in primary outcome (change in body weight) and secondary outcomes (cardiovascular risk factors, diet, physical activity, knowledge of CRC risk and psychosocial variables) were assessed by deprivation status. Results At baseline, education (P = 0.001), income (P < 0.001), spending on physical activity (P = 0.003) and success at previous weight loss attempts (P = 0.007) were significantly lower in the most deprived. At 12 months, no between group differences by deprivation status were detected for changes in primary and main secondary outcomes. Conclusions Despite potential barriers faced by the more deprived participants, primary and most secondary outcomes were comparable between groups, indicating that this intervention is unlikely to worsen health inequalities and is equally effective across socio‐economic groups.